Pengaruh K-Culture terhadap Perilaku Konsumsi Produk Impor Kosmetik Korea Selatan Jenis Serum - Ni Luh Gede Arma Ningsih; Ni Nyoman Reni Suasih (Universitas 45 Surabaya, 2024)
One of the daily needs for a woman is cosmetics. Skincare cosmetics are a very popular type of cosmetics over the past few years, one of which is serum so that the demand for this product is high. The change in consumption behavior of Indonesian people, especially skincare users, towards serum products to become more consumptive is caused by various factors, including cultural factors, especially K-Culture, consumption expenditure and income. The purpose of this study is to analyze and determine the simultaneous effect of K-Culture, consumption expenditure and income on the consumption behavior of imported South Korean cosmetic serum products and to analyze and determine the partial effect of K-Culture, consumption expenditure and income on the consumption behavior of imported South Korean cosmetic serum products in Denpasar City.